Improved techniques for hand-crafted soaps and detergents production - Oden Bella, M.G. (Technical Centre for Agricultural and Rural Cooperation, 2014)
With the soap and detergent market experiencing rapid growth in Africa, this clearly presented and illustrated guide provides a timely demonstration of improved techniques for their production. Using simple and effective methods, it describes the hand-crafted production of toilet soap, household soap, shampoo, and liquid and powdered detergent. An invaluable learning and development tool, the text is the perfect introduction for anyone wanting to start an income-generating project in this area.